تحليل وقياس اثر التغيرات في المجاميع النقدية على القيمة السوقية لبورصة الأوراق المالية في إطار السببية و التكامل المشترك دراسة حالة بورصة تونس خلال الفترة (2012-2017) - بن دحان, إلياس الأزهر (Recherches économiques et managériales; No 22 (2017): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(Décembre), 2018)
يهدف هذا البحث إلى دراسة اثر التغيرات في عرض النقود على بورصة الأوراق المالية التونسية من خلال تحليل اثر هذه التغيرات على قيمتها السوقية خلال الفترة (2012-2017) لاسيما ان معرفة مدى تأثير السياسة النقدية على بورصة الأوراق المالية، يمكن السلطة النقدية، من تصميم السياسة النقدية المناسبة لتوجيه الاستثمارات إلى القطاعات المختارة ولتحقيق هدف الدراسة تم استخدام منهجية التحليل القياسي للسلاسل الزمنية، حيث تم اختبار استقرار متغيرات الدراسة باستخدام اختبار ديكي - فولر الموسع ( ADF ) قبل تطبيق منهجية التكامل المشترك لجوهانسون لاختبار علاقة التوازن في المدى الطويل، كما تم استخدام اختبار السببية لجرانجر لتحديد اتجاه العلاقة السببية على المدى القصير، وقد توصلت الدراسة إلى وجود علاقة تكامل مشترك بين عرض النقود و القيمة السوقية لبورصة الأوراق المالية ،أما نتائج سببية جرانجر فتظهر وجود سببية قصيرة الأجل باتجاه واحد تتجه من عرض النقود إلى القيمة السوقية، وهذا يعني ان عرض النقود يسبب التغير في القيمة السوقية لبورصة الأوراق المالية التونسية وليس العكس . الكلمات المفتاحية : بورصة تونس،عرض النقود، القيمة السوقية، الإستقرارية، التكامل المشترك، السببية . Abstract : The aim of this study is to sudy the etffect of changes in the money supply on the Tunisian stock exchange by analyzing the effect of these changes on their Market Capitalization during the period 2012-2017. In particular Knowledge of impact of monetary policy on the stock exchange, policy-makers can design appropriate policies to direct investments to selected sectors . In order to achieve the objective of the study, the methodology of econometric analysis of time series was used. The stability of the study variables was tested using the Augmented Dickey-Fuller (ADF) test before applying Johansson’s co-integration methodology to test the long-term equilibrium relationship. The Granger’s causality test was used to determine the direction of the causal relationship in the short term . The study concluded that there is a common correlation between money supply and the Market Capitalization of the stock exchange, The results of Granger's causality show a unidirectional causality running fromthe money supply to Market Capitalization , which means that money supply causes Market Capitalization in the Tunisian stock exchange , not vice versa Key words: Tunis Stock Exchange, the money supply , Market Capitalization, Stationary , Cointegration, causality